Challenges to Implementing Environmental-DNA Monitoring in Namibia - Perry, Iain; Jâms, Ifan B.; Casas-Mulet, Roser; Hamutoko, Josefina; Marchbank, Angela; Lendelvo, Selma; Naomab, Erold; Mapani, Benjamin; Creer, Simon; Wanke, Heike; Durance, Isabelle; Kille, Peter (Frontiers in Environmental Science, 2022)
By identifying fragments of DNA in the environment, eDNA approaches present a promising tool for monitoring biodiversity cost-effectively. This is particularly pertinent for countries where traditional morphological, monitoring has been sparse. The first step to realising the potential of eDNA is to develop methodologies that are adapted to local challenges. Here, we test field and laboratory eDNA protocols (aqueous and sediment samples) in a range of semi-arid ecosystems in Namibia. We successfully gathered eDNA data on a broad suite of organisms at multiple trophic levels (including algae, invertebrates and bacteria) but identified two key challenges to the implementation of eDNA methods in the region: i) high turbidity requires a tailored sampling technique detailed herein and ii) identification of taxa by eDNA methods is currently constrained by a lack of reference data. We hope this work will guide the deployment of eDNA biomonitoring in the arid ecosystems that may be, to date, sparsely characterised.